2022
DOI: 10.1016/j.scitotenv.2021.150380
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral drug Umifenovir (Arbidol) in municipal wastewater during the COVID-19 pandemic: Estimated levels and transformation

Abstract: An indole derivative umifenovir (Arbidol) is one of the most widely used antiviral drugs for the prevention and treatment of COVID-19 and some other viral infections. The purpose of the present study was to shed light on the transformation processes of umifenovir in municipal wastewater, including disinfection with active chlorine, as well as to assess the levels of the antiviral drug and its metabolites entering and accumulating in natural reservoirs under conditions of the SARS-CoV-2 pandemic. The combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…The concentrations of ritonavir and lopinavir were much lower than those in the receiving rivers of Guangdong, China ( Yao et al, 2021 ). The arbidol concentration levels were similar to that reported for the Khatoritsa River, Russia ( Ul'yanovskii et al, 2022 ). Due to the poor removal efficiency of the three antiviral drugs in WWTPs ( Ul'yanovskii et al, 2022 ; Yao et al, 2021 ), the manifold increase in their emission requires further investigation.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The concentrations of ritonavir and lopinavir were much lower than those in the receiving rivers of Guangdong, China ( Yao et al, 2021 ). The arbidol concentration levels were similar to that reported for the Khatoritsa River, Russia ( Ul'yanovskii et al, 2022 ). Due to the poor removal efficiency of the three antiviral drugs in WWTPs ( Ul'yanovskii et al, 2022 ; Yao et al, 2021 ), the manifold increase in their emission requires further investigation.…”
Section: Resultssupporting
confidence: 88%
“… Yao et al (2021) and Kumari and Kumar (2022) validated the high ecological risks to the aquatic environment caused by ritonavir and lopinavir. Ul'yanovskii et al (2022) found a pronounced accumulation of arbidol in river bottom sediments, which could be a source of secondary pollution. The impacts of the pharmaceuticals used for COVID-19 treatment on the aquatic environment are of increasing concern and merit further investigation ( Bandala et al, 2021 ).…”
Section: Introductionmentioning
confidence: 95%
“…Some of the journals that published papers on the first query have more than one paper. Indeed, Science of the Total Environment dedicated a special issue on SARS-CoV-2 and collected 15 papers [1], [4], [5], [10], [16], [24], [25], [31]- [33], [36], [43], [63], [83], [84]. The other two journals that attracted papers connected with the first query are Resources, Conservation and Recycling [81], [82], [85], [86], [102] and Environmental Science and Pollution Research [14], [21], [27], [44], [48], each of them having five papers published.…”
Section: Resultsmentioning
confidence: 99%
“…Since the outbreak of the pandemic, elevated consumption of umifenovir (an antiviral drug) has led to its presence at 1 µg/L in municipal wastewater. This drug forms a wide range of DBPs when it reacts with sodium hypochlorite, most of them being Br-DBPs with bromoform as the dominant species (Ul’yanovskii et al, 2022 ). It is well known that the consumption of various antibiotics and other life-saving medicines has been rising during the pandemic; these compounds will eventually end up in the WWTPs and waterbodies (Goel 2015 ).…”
Section: Dbp Formation By Disinfection Of Hospital Surfaces and Wastewatermentioning
confidence: 99%